Ranking the performance of tennis players: an application to women`s professional tennis - Blackburn, M. L. (Journal of Quantitative Analysis in Sports, 2013)
Paired-comparison models have been previously used in the literature to assess the relative performance of tennis players over a given period of time. In this paper, I discuss how the rankings of tennis players can be modified to address variations in the importance of tennis tournaments, and concerns about under-participation over the tennis season. The methods are applied to the 2011 WTA season, where the WTA-ranked number one player Caroline Wozniacki was often criticized for not being the true top player. The alternative rankings proposed here indicate that Petra Kvitova was the top player in 2011, with Serena Williams a close second. These rankings do appear to perform better in predicting match probabilities in early 2012 than methods based on the official rankings.